Ensino de evolução e a pandemia da Covid-19: uma sequência didática investigativa - Arcanjo, Élique do Carmo (2024)
Teaching evolution is essential to understanding the origin of the diversity of life forms and the relationships between living beings. It is also a powerful tool for developing critical thinking in those who study it, since its practice is permeated by intense moments of analysis and reflection. However, several studies point to a series of difficulties, both on the part of teachers and students, when biology classes address evolution. Based on this finding, and also observing the context of the pandemic caused by the new coronavirus, the development and application of an investigative teaching sequence was proposed for teaching key concepts of evolution, relating them to Covid-19. The theme of didactic sequence, as well as its potential in teaching and learning processes, has been addressed by many authors. Teaching by inquiry, in turn, is a pedagogical approach that places students at the center of the learning process, with the teacher playing the role of facilitator of knowledge who must provide conditions for students to act as protagonists in the construction of knowledge. The qualitative research was conducted in a public school in the state of Espírito Santo, located in the city of Cariacica, with the participation of students in the 1st year of high school. Throughout the methodological process, the students conducted research related to the evolution of COVID-19, focusing on three axes, seeking to correlate with the evolutionary concepts of mutation, natural selection and adaptation: evolution of the number of deaths in Espírito Santo, emergence of SARS-Cov-2 variants, and vaccines against COVID-19. Through the analysis of observations, behaviors and content produced and collected throughout the process, as well as responses to the pre-test and post-test, and the opinion survey, it was possible to verify that the proposed objectives were achieved. It was observed that the students are able to draw a parallel between the evolution of other species and the evolution of viruses, although the justifications vary in clarity and precision. After applying the didactic sequence, progress was noted in most of the items evaluated, related to the key concepts of evolution and its relationship with COVID-19. Regarding the use of the investigative didactic sequence resource, there was a favorable response from the students. The need to seek different strategies was also observed, taking into account the diversity of learning methods among students.